Podlasie — gdzie religia spotyka magię - Weber, Eryk (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article presents the results of the field and reporter work on folk healers, which I carried out in the region of Podlasie. In my article I want to explain the issues of discourse in which magic and religion are entangled, and depict as they relate to the local residents. It also has the task of documenting specific magical techniques used by healers called “Szeptuchy”. I examined those aspects personally by visiting any case that is mentioned in the article and by carrying out appropriate conversations and being the subject to their treatment. I also witnessed and was the object of those techniques, therefore, I was able to get closer to the true nature of the mentioned unique in the country phenomenon. It seems that this phenomenon should remain intact in possibly every aspect and cherished in its specific isolation and purity, unsullied by the contemporary globalist will of profit.